(untitled) (مجلة إحالات, 2026)
Popular literature is rich with various literary forms, and proverbs are among them. They are a distilled essence of long human experiences, making them deeply connected to popular life. Proverbs are among the most authentic forms of expression in depicting the lives of individuals in all aspects of their existence and reflecting the types of relationships between them. They truly represent the finest words, the cream of speech, the essence of ideas, the result of experiences, and a mirror of everyday life. Algerian proverbs have addressed numerous issues, documenting various customs and traditions prevalent in society. The image of the "mother" is one of the topics that these proverbs have presented in the best and most eloquent way.This paper aims to shed light on the portrayal of the mother in Algerian popular proverbs and to explore the representations of her, which range from encouraging respect and honoring mothers to warning against disrespect and disobedience.